Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1136/bjo.2009.167775
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of corneal aberrations for customisation of intraocular lens asphericity: impact on quality of vision after micro-incision cataract surgery

Abstract: Individual selection of IOL asphericity with a preoperative corneal SA measurement allowed control of final ocular SA. Such customisation improves mesopic contrast sensitivity, and leads to better objective quality of vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
5
27
0
Order By: Relevance
“…The results showed that contrast sensitivity in the mesopic and mesopic with glare conditions at middle and high spatial frequencies was better in the experimental vs. the RA group. This finding is in agreement with a similar recent study by Nochez et al [8] in which patients were implanted with zero-aberration Acri.Smart 46LC lenses (the reference group) or Acri.Smart36A lenses (experimental group) based on pre-surgical corneal spherical aberration. These authors showed that under mesopic conditions at high spatial frequencies, the contrast sensitivity was significantly better in the experimental group.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results showed that contrast sensitivity in the mesopic and mesopic with glare conditions at middle and high spatial frequencies was better in the experimental vs. the RA group. This finding is in agreement with a similar recent study by Nochez et al [8] in which patients were implanted with zero-aberration Acri.Smart 46LC lenses (the reference group) or Acri.Smart36A lenses (experimental group) based on pre-surgical corneal spherical aberration. These authors showed that under mesopic conditions at high spatial frequencies, the contrast sensitivity was significantly better in the experimental group.…”
Section: Discussionsupporting
confidence: 94%
“…However, we found a mean absolute predictive error of 0.046 ± 0.079 μm for postoperative SA in agreement with Nochez et al [8] (0.040 ± 0.047 μm) and very similar to that of Packer et al [9] (0.058 ± 0.056 µm) who tested three different IOLs (AO, AcrySofIQ and Tecnis). Minor variations in predictive value were explained as a result of the postoperative aperture size being limited by the capsulorhexis and by variations in pupil dilatation [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate statistically significant differences between eyes with increased aMTF and those with decreased aMTF in the vertical coma and tetrafoil ( Table 3). Previous studies found that corneal SA and coma did not change significantly with corneal incision and that other HOAs also did not change, especially after micro-incision cataract surgery [15,29]. Therefore, it could be assumed that relatively high preoperative corneal HOA might be a negative predictive factor of optical outcomes using aspheric IOLs.…”
Section: Discussionmentioning
confidence: 91%
“…However, there is no clear target SA for optimal visual outcome [12]. Some studies indicated that complete correction of SA improved visual performance, but some model-eye studies could not indicate best visual quality for a fully corrected SA [12][13][14][15]. Inter-subject variability and interaction of the different sources of optical aberration may also make it difficult to determine the ideal SA of an IOL [16,17].…”
Section: Introductionmentioning
confidence: 99%